Analisis efisiensi produksi bokar dan faktor-faktor yang mempengaruhinya (studi kasus di Desa Muhajirin Kecamatan Jambi Luar Kota Kabupaten Muaro Jambi) - Imam Prasetyo; M. Ridwansyah; Rosmeli Rosmeli (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2021)
This study aims to: 1) analyze the production factors that affect the production of bokar, 2) analyze the level of technical, allocative and economic efficiency of bokar production factors in Muhajirin Village, Jambi Luar Kota District, Muaro Jambi Regency. The data used in this study are primary data and secondary data. The model used in this study was a multiple linear regression model. The result showed that labor and the amount of use superior seeds had no significant effect on bokar production in Muhajirin Village, while the plant age and land area variables had a significant effect on bokar production in Muhajirin Village. The average value of technical efficiency was 0,754, which means that the bokar production bussines in Muhajirin Village was technically efficient, the value of allocative efficiency was -1,65 and the economic efficiency was -1,25. This shows that the bokar production business in Muhajirin Village has not reached the value of economic efficiency. Keywords : Bokar production, The labor, Plant age, Land area, The amount of use of superior seeds